Comparative efficacy of human papillomavirus vaccines: systematic review and network meta-analysis - Rui Lin; Hui Jin; Xin Fu (Taylor & Francis Group, 2023)
ABSTRACTObjectives Despite their use, differences in human papillomavirus (HPV) vaccine efficacies remain uncertain. This study assesses efficacy differences among bivalent, quadrivalent, and nine-valent HPV (2vHPV, 4vHPV, and 9vHPV) vaccines.Methods PubMed, Web of Science, Embase, and the Cochrane Library were searched for randomized controlled trials comparing HPV vaccine efficacy against persistent infection (≥6 months) and cervical intraepithelial neoplasia grade 2 or worse (CIN2+). Network meta-analysis yielded direct and indirect comparisons. Risk ratios (RRs) and 95% confidence intervals (95% CIs) were reported, and robustness was evaluated via sensitivity analysis.Results In 11 randomized controlled trials with 58,881 healthy women, for persistent infection with HPV 16, 9vHPV was most effective at 97% (RR = 0.03, 95% CI: 0.01-0.08); for HPV 18, 2vHPV (Cecolin) was most effective at 98% (RR = 0.02, 95% CI: 0.00-0.29); for CIN2+ associated with HPV 16 and 18, 4vHPV was most effective at 99% (RR = 0.01, 95% CI: 0.00-0.10) and 97% (RR = 0.03, 95% CI: 0.00-0.45), respectively; for persistent infection with HPV 31, 33, 45, 52, and 58, 9vHPV was ≥ 95% effective; both 2vHPV vaccines were cross-effective against HPV 31, 33, and 45; and 4vHPV was cross-effective against HPV 31.Conclusions HPV vaccine efficacies differ for different HPV types. Additional data are needed to determine the cross-efficacy of 2vHPV (Cecolin).